2011
DOI: 10.1080/15533174.2011.555868
|View full text |Cite
|
Sign up to set email alerts
|

Triad CNT-NPs/Polymer Nanocomposites: Fabrication, Characterization, and Preliminary Antimicrobial Study

Abstract: We report a comprehensive study of fabrication of advanced CNT-AgNPs/Polymer based nanocomposites (NCs) including structural (UV-Vis, FT-Raman, EDS, and XRD), morphological (FE-SEM, AFM, and TEM), thermal (TGA and DSC), and preliminary antimicrobial properties. Electrostatic attraction was utilized to incorporate silver nanoparticles (AgNPs) on carboxylic group functionalized single walled carbon nanotubes (SWCNTs). This was achieved by in-situ reduction of AgNO 3 and immobilization of AgNPs using NaBH 4 (redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Similarly, chitosan-CNT hybrid showed excellent antimicrobial activities against bacteria and fungi [ 9 ]. Other CNTs antimicrobial hybrids include ZnO coated MWCNTs (ZnO/MWCNTs) [ 13 ], Triad CNT-NPs/Polymer nanocomposites [ 11 ], functionalized MWCNTs-CdS and functionalized-MWCNTs-Ag2S [ 31 ], and CdTe QDs/single-walled aluminosilicate nanotubes [ 32 ]. Furthermore, Cefalexin-immobilized multi-walled CNTs have been found to broadly enhance the antimicrobial activities against a wide range of pathogens including E. coli, P. aeruginosa, S. aureus and Bacillus subtilis [ 8 ] as shown in Table 1 .…”
Section: Broad Spectrum Nanoparticle-antimicrobial Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, chitosan-CNT hybrid showed excellent antimicrobial activities against bacteria and fungi [ 9 ]. Other CNTs antimicrobial hybrids include ZnO coated MWCNTs (ZnO/MWCNTs) [ 13 ], Triad CNT-NPs/Polymer nanocomposites [ 11 ], functionalized MWCNTs-CdS and functionalized-MWCNTs-Ag2S [ 31 ], and CdTe QDs/single-walled aluminosilicate nanotubes [ 32 ]. Furthermore, Cefalexin-immobilized multi-walled CNTs have been found to broadly enhance the antimicrobial activities against a wide range of pathogens including E. coli, P. aeruginosa, S. aureus and Bacillus subtilis [ 8 ] as shown in Table 1 .…”
Section: Broad Spectrum Nanoparticle-antimicrobial Agentsmentioning
confidence: 99%
“…The NPs physiochemical properties are highly diverse in nature and are highly applicable in biomedical field including antimicrobial and drug delivery [ 6 , 8 , 9 ]. Some examples of these biomedical NPs include silver nanoparticles (AgNPs) [ 10 ], carbon nanotubes (CNTs) [ 11 ], gold NPs (AuNPs) [ 12 ], zinc oxide NPs (ZnO-NPs) [ 13 ], and iron oxide NPs (FeO-NPs) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Although MWCNTs have been correlated with ecotoxical effects, 33 DNA damage, 34 and pulmonary inflammation, 35 recent studies revealed that MWCNTs can be used in materials designed for water disinfection and purification 36 and coupled with AgNPs for photodegradation processes 37 or as fillers with antimicrobial activity. 38 An optimum antimicrobial membrane design with possible uses in water purification should involve low-cost materials and increased lifetime service. Thus, the aim of our design is to try to satisfy these actual social and economic requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites based on MWCNTs have gained intense interest owing to their improved properties, namely, mechanical behavior, thermal and electrical conductivities, and also high chemical stability. , Although MWCNTs have been correlated with ecotoxical effects, DNA damage, and pulmonary inflammation, recent studies revealed that MWCNTs can be used in materials designed for water disinfection and purification and coupled with AgNPs for photodegradation processes or as fillers with antimicrobial activity …”
Section: Introductionmentioning
confidence: 99%